The nature of neural object representations during dynamic occlusion. (August 2022) - Teichmann, Lina; Moerel, Denise; Rich, Anina N.; Baker, Chris I.
Abstract: Objects disappearing briefly from sight due to occlusion is an inevitable occurrence in everyday life. Yet we generally have a strong experience that occluded objects continue to exist, despite the fact that they objectively disappear. This indicates that neural object representations must be maintained during dynamic occlusion. However, it is unclear what the nature of such representation is and in particular whether it is perception-like or more abstract, for example, reflecting limited features such as position or movement direction only. In this study, we address this question by examining how different object features such as object shape, luminance, and position are represented in the brain when a moving object is dynamically occluded. We apply multivariate decoding methods to Magnetoencephalography (MEG) data to track how object representations unfold over time. Our methods allow us to contrast the representations of multiple object features during occlusion and enable us to compare the neural responses evoked by visible and occluded objects. The results show that object position information is represented during occlusion to a limited extent while object identity features are not maintained through the period of occlusion. Together, this suggests that the nature of object representations during dynamic occlusion is different from visual representations during perception.